The effectiveness of the disposal of Non-Current assets in the public sector, a case study of Tanzania Revenue Authority. - Celestine, Ruth. (Mzumbe University, 2024)
A Dissertation Submitted in Partial Fulfilment of the Requirement for the Degree of Master of Business Administration in Corporate Management (MBA) at Mzumbe University Dar-es-salaam Campus